High-strength wear-resistant metal connecting piece and processing technology thereof

By optimizing carbonitriding and surface coating treatment using a specific mass ratio of composite complexing agent and chemical plating solution, the wear resistance and strength issues of metal connectors in high-wear environments were solved, achieving higher wear resistance and strength.

CN120989550APending Publication Date: 2025-11-21SUZHOU QILONGDA METAL PRODUCTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510969359.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

In existing technologies, metal connectors suffer from uneven surface treatment, carbon-nitrogen ratio imbalance, difficulty in controlling rare earth content, and weak adhesion of chemical plating in high-wear environments, resulting in insufficient wear resistance and strength.

Method used

By using a composite complexing agent and chemical plating solution with a specific mass ratio, the carbonitriding process is optimized through the synergistic effect of glycine, urea and rare earth element lanthanum. Combined with specific temperature and atmosphere conditions, surface coating treatment is carried out to improve the wear resistance and strength of metal connectors.

Benefits of technology

It effectively improves the carbonitriding efficiency and interfacial bonding of metal connectors, enhances wear resistance and strength, and solves the shortcomings of existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of metal connecting pieces, in particular to a high-strength wear-resistant metal connecting piece and a machining process thereof. Comprising the following steps that 1, basic steel is subjected to rolling, heat treatment and cooling, and a basic metal connecting piece is obtained; 2, a composite complexing agent is sprayed to the surface of the base metal connecting piece, pretreatment and carbonitriding are carried out, and a base metal connecting piece A is obtained; 3, the basic metal connecting piece A is subjected to surface coating treatment and post-treatment; therefore, the metal connecting piece is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of metal connecting pieces, in particular to a high-strength wear-resistant metal connecting piece and a processing technology thereof. BACKGROUND

[0002] In modern life, metal connecting pieces are widely used as basic components, especially in bicycle transmission systems, industrial air conditioner compressors and other equipment, which directly affect the quality and service life of products. Therefore, people are increasingly strict with the performance and quality of metal connecting pieces, which has become a hot topic of current research.

[0003] In the bicycle transmission system, metal connecting pieces such as splines and gears are subjected to long-term load operation in a complex environment of high wear, high pressure, dry and wet, and the quality and service life gradually decline. Therefore, in order to solve the above problems, it is necessary to improve the strength and wear resistance of metal connecting pieces, and further improve the product quality and service life.

[0004] In the prior art, carbonitriding is used to penetrate carbon and nitrogen elements into the surface of the metal to form a hardened layer, thereby improving the wear resistance and strength of the metal connecting piece. However, the following problems may occur during actual preparation: first, the surface treatment is single, and polishing and chemical cleaning cannot completely remove the oxide film on the surface of the metal. During the carbonitriding process, uneven diffusion may occur, resulting in stress concentration and causing cracks or even breakage. Second, during the carbonitriding process, the carbon and nitrogen source supply method is single, and gases such as ammonia and methanol are often used, making it difficult to accurately control the carbon and nitrogen ratio, resulting in an imbalance in the carbon and nitrogen ratio of the penetration layer, and the wear resistance and strength cannot be improved to the ideal effect. Third, although rare earth can promote the diffusion of carbon and nitrogen, the amount of rare earth cannot be accurately controlled. Excessive rare earth may form a diffusion barrier, which may reduce the penetration efficiency of carbon and nitrogen and reduce the wear resistance and strength.

[0005] Chemical plating is an important means of surface coating, which can improve the wear resistance and strength of the metal surface. However, during the chemical plating process, there are still problems such as poor stability and low deposition rate, which may result in weak adhesion between the plating layer and the substrate, easy peeling and affect the product quality.

[0006] In summary, it is of great significance to solve the above problems and prepare a high-strength wear-resistant metal connecting piece. SUMMARY

[0007] The present application aims to provide a high-strength wear-resistant metal connecting piece and a processing technology thereof to solve the problems mentioned in the background.

[0008] To solve the above technical problems, the present application provides the following technical solutions: A processing technology for a high-strength wear-resistant metal connecting piece, comprising the following steps: Step 1: rolling, heat treatment, cooling of the base steel material to obtain a base metal connector; Step 2: spraying a composite complexing agent on the surface of the base metal connector, pretreatment, carbonitriding to obtain a base metal connector A; Step 3: surface coating treatment of the base metal connector A, post-treatment to obtain a metal connector.

[0009] More preferably, the raw material of the base steel material includes the following elements, in terms of mass percentage: 0.65%~0.70% carbon, 1.00%~1.25% silicon, 0.45%~0.60% manganese, ≤0.025% sulfur, ≤0.025% phosphorus, 0.40%~0.50% molybdenum, 0.10%~0.30% chromium, 0.15%~0.25% vanadium, and the rest is iron.

[0010] More preferably, the preparation process of the composite complexing agent is as follows: mixing glycine, urea, lanthanum lactate, ethylenediaminetetraacetic acid disodium salt, and deionized water according to a mass ratio of 2:1:0.3~0.5:0.05~0.15:40~50, adding acetic acid to adjust the pH to 4.5~5.5 to obtain the composite complexing agent.

[0011] In the scheme, the composite complexing agent is used with a specific mass ratio and at a specific temperature, and the glycine and urea in the composite complexing agent synergistically improve the carbonitriding efficiency with the rare earth element lanthanum, further improving the wear resistance and strength of the metal connector; the surface coating treatment is performed by using a chemical plating solution with specific components, further improving the wear resistance and strength of the metal connector.

[0012] In the composite complexing agent, the specific mass of glycine and urea is ultrasonically treated at a temperature of 75~85℃, the glycine is complexed with iron ions to form a soluble complex, the surface of the base metal connector is cleaned to prevent uneven carbonitriding during the carbonitriding process, stress concentration, and even cracking or breaking; at a temperature of 140~160℃, the glycine and urea begin to provide carbon and nitrogen sources for subsequent carbonitriding; at a temperature of 240~400℃, the rare earth forms a complex, which is then decomposed, adsorbed on the surface, promotes the diffusion of carbon and nitrogen elements, refines the grains, and improves the carbonitriding efficiency.

[0013] It should be noted that the mass of lanthanum lactate in the complexing agent should not be too much, and excessive rare earth elements will form a diffusion barrier, hinder the diffusion of carbon and nitrogen elements, reduce the interfacial bonding force, and decrease the surface hardness, further reducing the wear resistance and strength; at the same time, the mass control of glycine is also crucial, on the one hand, when the mass of glycine is too low, the dual role of glycine as a complexing agent and carbon source is insufficient, the oxide film is not completely removed, the carbon-nitrogen ratio is imbalanced, the carbon-nitrogen co-diffusion efficiency is reduced, and the wear resistance and strength are further reduced; on the other hand, when the mass of glycine is too high, its strong complexing effect will over-coordinate with rare earth ions, reduce the activity of rare earth, hinder the diffusion of carbon and nitrogen, and possibly form a glycine-rich residual layer at the interface, weaken the metallurgical bonding between the co-diffusion layer and the matrix, and result in the decrease of the bonding force and mechanical properties.

[0014] Among them, the chemical plating solution prepared by the specific components, surface coating treatment, and a small amount of rare earth elements can improve the deposition rate and stability of the chemical plating solution, and the rare earth elements in the chemical plating layer can form a chemical bond with the carbonitride in the co-diffusion layer, enhance the metallurgical bonding between the plating layer and the co-diffusion layer, avoid the peeling of the coating, and further improve the wear resistance and strength.

[0015] More preferably, in step 1, the rolling temperature is 950-1050℃; in the heat treatment, the process parameters include: the annealing temperature is 850-920℃, the cooling temperature is 550-650℃, the quenching temperature is 850-900℃, the quenching medium is brine; the tempering temperature is 200-250℃.

[0016] More preferably, in step 2, the process parameters for spraying are: the spraying flow rate is 0.5-1.8ml / min; the spraying time is 5-10min; The process parameters for the pretreatment are: the ultrasonic treatment temperature is 75-85, the ultrasonic treatment time is 30-60min; the atmosphere is nitrogen atmosphere, the drying temperature is 140-160℃, the drying time is 1-2h; the temperature rising temperature is 240-400℃; the holding time is 1-2h; The process parameters for the carbon-nitrogen co-diffusion are: the atmosphere is mixed gas; the voltage is 450-550V; the frequency is 75-85Hz; the carbon-nitrogen co-diffusion temperature is 400-580℃; the holding time is 5-6h.

[0017] More preferably, the initial volume ratio of the mixed gas is 1:4-5 of nitrogen and hydrogen; and the volume ratio of the mixed gas is dynamically adjusted to 4-5:1.

[0018] More preferably, in step 3, the surface coating treatment process is as follows: the base metal connector A is immersed in an aqueous hydrochloric acid solution, pickled and activated at 55-65 DEG C for 10-15 min, washed with deionized water, and chemical plating is carried out at 80-90 DEG C for 1-3 h using a chemical plating solution. The post-treatment process is as follows: heat treatment under nitrogen atmosphere at 350-450 DEG C for 0.5-1.5 h.

[0019] In a further aspect, in the aqueous hydrochloric acid solution, the mass ratio of hydrochloric acid to deionized water is 1:5-6.

[0020] More preferably, the preparation process of the chemical plating solution is as follows: nickel sulfate, sodium hypophosphite, lactic acid, succinic acid, lanthanum nitrate, and thiourea are added to deionized water, the pH is adjusted to 5.2-5.7, and the mixture is mixed at 35-45 DEG C to obtain the chemical plating solution.

[0021] More preferably, in the raw materials of the chemical plating solution, the following components are included: 27-29 parts of nickel sulfate, 25-27 parts of sodium hypophosphite, 20-24 parts of lactic acid, 13-17 parts of succinic acid, 0.05-0.08 parts of lanthanum nitrate, 0.001-0.003 parts of thiourea, and 120-150 parts of deionized water.

[0022] In a further aspect, the amount of lanthanum nitrate added to the chemical plating solution needs to be synergistically controlled with the lanthanum lactate in the complexing agent, and the total rare earth content should be controlled at 0.05wt%-0.1wt% of the total metal connector to avoid negative effects caused by excessive amounts.

[0023] Compared with the prior art, the beneficial effects of the present application are: By using the complexing agent with a specific mass ratio and at a specific temperature, the glycine and urea synergistically improve the carbonitriding efficiency with the rare earth element lanthanum, further improving the wear resistance and strength of the metal connector; and by using the chemical plating solution with specific components for surface coating treatment, the interfacial bonding strength is improved, further improving the wear resistance and strength of the metal connector. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present application will be described below in a clear and complete manner. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.

[0025] It should be noted that the following parts are quality parts, and there is no special restriction on the manufacturers of all raw materials involved in the application, which exemplarily includes: in the following examples, the CAS number of glycine is 56-40-6; the CAS number of urea is 57-13-6; the CAS number of lanthanum lactate is 55729-42-3; the CAS number of disodium ethylenediaminetetraacetate is 139-33-3; the CAS number of nickel sulfate is 7786-81-4; the CAS number of sodium hypophosphite is 10039-56-2; the CAS number of lactic acid is 50-21-5; the CAS number of succinic acid is 110-15-6; the CAS number of lanthanum nitrate is 10277-43-7; the CAS number of thiourea is 62-56-6.

[0026] The following examples are particularly described: (1) The base steel material includes the following elements, in terms of mass percentage: 0.67% carbon, 1.12% silicon, 0.52% manganese, 0.025% sulfur, 0.025% phosphorus, 0.45% molybdenum, 0.2% chromium, 0.20% vanadium, and the remainder is iron; (2) The initial volume ratio of the mixed gas is 1:4.5 of nitrogen and hydrogen; and the volume ratio of the mixed gas is dynamically adjusted to 4.5:1; (3) In the aqueous hydrochloric acid solution, the mass ratio of hydrochloric acid to deionized water is 1:5.5; (4) The total rare earth content should be controlled at 0.08wt% of the total metal connector.

[0027] Example 1: A processing technology of a high-strength wear-resistant metal connector, comprising the following steps: Step 1: The base steel material is rolled at 1000℃, then annealed at 900℃, cooled to 600℃, quenched at 875℃ with salt water as the quenching medium, and finally tempered at 225℃, cooled to obtain a base metal connector; Step 2: (1) Glycine, urea, lanthanum lactate, disodium ethylenediaminetetraacetate, and deionized water are mixed in a mass ratio of 2:1:0.4:0.1:45, acetic acid is added to adjust the pH to 5.0 to obtain a composite complexing agent; (2) The composite complexing agent is sprayed on the surface of the base metal connector at 1.1ml / min for 8min, ultrasonic treated at 80℃ for 45min, dried at 150℃ under nitrogen atmosphere for 1.5h, heated to 320℃ and kept for 1.5h; (3) The mixed gas is introduced, and carbonitriding is carried out at 490℃ with a voltage of 500V and a frequency of 80Hz for 5.5h to obtain a base metal connector A; Step 3: (1) Add 28 parts nickel sulfate, 26 parts sodium hypophosphite, 22 parts lactic acid, 15 parts succinic acid, 0.065 parts lanthanum nitrate, and 0.002 parts thiourea to 135 parts deionized water, adjust the pH to 5.5, mix at 40°C to obtain a chemical plating solution; (2) Immerse the base metal connector A in hydrochloric acid aqueous solution, acid-wash and activate at 60°C for 12.5 min, wash with deionized water, chemically plating at 85°C for 2 h using the chemical plating solution, and then heat-treat at 400°C for 1 h under a nitrogen atmosphere to obtain the metal connector.

[0028] Example 2: A processing method for a high-strength, wear-resistant metal connector, comprising the following steps: Step 1: Roll the base steel at 1000℃, then anneal at 900℃, cool to 600℃, quench at 875℃ using brine as the quenching medium, and finally temper at 225℃ and cool to obtain the base metal connector. Step 2: (1) Glycine, urea, lanthanum lactate, disodium ethylenediaminetetraacetate, and deionized water are mixed in a mass ratio of 2:1:0.3:0.05:45. Acetic acid is added to adjust the pH to 5.0 to obtain a composite complexing agent. (2) The composite complexing agent is sprayed onto the surface of the base metal connector at a rate of 1.1 ml / min for 8 min. The surface is ultrasonically treated at 80°C for 45 min, dried at 140°C for 1 h under a nitrogen atmosphere, heated to 240°C and kept warm for 1 h. (3) A mixed gas is introduced, and carbonitriding is performed at 400°C with a voltage of 500V and a frequency of 80Hz and kept warm for 5 h to obtain the base metal connector A. Step 3: (1) Add 27 parts nickel sulfate, 25 parts sodium hypophosphite, 20 parts lactic acid, 13 parts succinic acid, 0.05 parts lanthanum nitrate, and 0.001 parts thiourea to 120 parts deionized water, adjust the pH to 5.2, mix at 40°C to obtain a chemical plating solution; (2) Immerse the base metal connector A in hydrochloric acid aqueous solution, acid-wash and activate at 60°C for 12.5 min, wash with deionized water, chemically plating at 85°C for 2 h using the chemical plating solution, and then heat-treat at 400°C for 1 h under a nitrogen atmosphere to obtain the metal connector.

[0029] Example 3: A processing method for a high-strength, wear-resistant metal connector, comprising the following steps: Step 1: Roll the base steel at 1000℃, then anneal at 900℃, cool to 600℃, quench at 875℃ using brine as the quenching medium, and finally temper at 225℃ and cool to obtain the base metal connector. Step 2: (1) Glycine, urea, lanthanum lactate, disodium ethylenediaminetetraacetate, and deionized water are mixed in a mass ratio of 2:1:0.5:0.15:45. Acetic acid is added to adjust the pH to 5.0 to obtain a composite complexing agent. (2) The composite complexing agent is sprayed onto the surface of the base metal connector at a rate of 1.1 ml / min for 8 min. The surface is ultrasonically treated at 80°C for 45 min, dried at 160°C for 2 h under a nitrogen atmosphere, heated to 400°C and kept at that temperature for 2 h. (3) A mixed gas is introduced, and carbonitriding is performed at 580°C with a voltage of 500V and a frequency of 80Hz for 6 h to obtain the base metal connector A. Step 3: (1) Add 29 parts nickel sulfate, 27 parts sodium hypophosphite, 24 parts lactic acid, 17 parts succinic acid, 0.08 parts lanthanum nitrate, and 0.003 parts thiourea to 150 parts deionized water, adjust the pH to 5.7, mix at 40°C to obtain a chemical plating solution; (2) Immerse the base metal connector A in hydrochloric acid aqueous solution, pickle and activate at 60°C for 12.5 min, wash with deionized water, perform chemical plating at 85°C for 2 h using the chemical plating solution, and then heat treat at 400°C for 1 h under a nitrogen atmosphere to obtain the metal connector.

[0030] Comparative Example 1: Based on Example 1, the lanthanum lactate in the composite complexing agent was removed, while the rest of the process remained unchanged. Specifically: Step 1: Roll the base steel at 1000℃, then anneal at 900℃, cool to 600℃, quench at 875℃ using brine as the quenching medium, and finally temper at 225℃ and cool to obtain the base metal connector. Step 2: (1) Glycine, urea, disodium ethylenediaminetetraacetate and deionized water are mixed in a mass ratio of 2:1:0.1:45. Acetic acid is added to adjust the pH to 5.0 to obtain a composite complexing agent; (2) The composite complexing agent is sprayed onto the surface of the base metal connector at 1.1 ml / min for 8 min. It is then ultrasonically treated at 80℃ for 45 min, dried at 150℃ for 1.5 h under a nitrogen atmosphere, heated to 320℃ and kept at that temperature for 1.5 h; (3) A mixed gas is introduced, and carbonitriding is performed at 490℃ with a voltage of 500V and a frequency of 80Hz and kept at that temperature for 5.5 h to obtain the base metal connector A; Step 3: (1) Add 28 parts nickel sulfate, 26 parts sodium hypophosphite, 22 parts lactic acid, 15 parts succinic acid, 0.065 parts lanthanum nitrate, and 0.002 parts thiourea to 135 parts deionized water, adjust the pH to 5.5, mix at 40°C to obtain a chemical plating solution; (2) Immerse the base metal connector A in hydrochloric acid aqueous solution, acid-wash and activate at 60°C for 12.5 min, wash with deionized water, chemically plating at 85°C for 2 h using the chemical plating solution, and then heat-treat at 400°C for 1 h under a nitrogen atmosphere to obtain the metal connector.

[0031] Comparative Example 2: Based on Example 1, glycine and urea were removed from the composite complexing agent, while the rest of the process remained unchanged. Specifically: Step 1: Roll the base steel at 1000℃, then anneal at 900℃, cool to 600℃, quench at 875℃ using brine as the quenching medium, and finally temper at 225℃ and cool to obtain the base metal connector. Step 2: (1) Mix lanthanum lactate, disodium ethylenediaminetetraacetate, and deionized water in a mass ratio of 0.4:0.1:45, add acetic acid to adjust the pH to 5.0, and obtain a composite complexing agent; (2) Spray the composite complexing agent at 1.1 ml / min for 8 min onto the surface of the base metal connector, sonicate at 80°C for 45 min, dry at 150°C for 1.5 h under nitrogen atmosphere, raise the temperature to 320°C and keep it at that temperature for 1.5 h; (3) Introduce the mixed gas, carbonitride at 490°C with a voltage of 500V and a frequency of 80Hz and keep it at that temperature for 5.5 h to obtain the base metal connector A; Step 3: (1) Add 28 parts nickel sulfate, 26 parts sodium hypophosphite, 22 parts lactic acid, 15 parts succinic acid, 0.065 parts lanthanum nitrate, and 0.002 parts thiourea to 135 parts deionized water, adjust the pH to 5.5, mix at 40°C to obtain a chemical plating solution; (2) Immerse the base metal connector A in hydrochloric acid aqueous solution, acid-wash and activate at 60°C for 12.5 min, wash with deionized water, chemically plating at 85°C for 2 h using the chemical plating solution, and then heat-treat at 400°C for 1 h under a nitrogen atmosphere to obtain the metal connector.

[0032] Comparative Example 3: Based on Example 1, the excess of lanthanum lactate in the composite complexing agent was adjusted, while the rest of the process remained unchanged. Specifically: Step 1: Roll the base steel at 1000℃, then anneal at 900℃, cool to 600℃, quench at 875℃ using brine as the quenching medium, and finally temper at 225℃ and cool to obtain the base metal connector. Step 2: (1) Glycine, urea, lanthanum lactate, disodium ethylenediaminetetraacetate, and deionized water are mixed in a mass ratio of 2:1:1.5:0.1:45. Acetic acid is added to adjust the pH to 5.0 to obtain a composite complexing agent. (2) The composite complexing agent is sprayed onto the surface of the base metal connector at a rate of 1.1 ml / min for 8 min. The surface is ultrasonically treated at 80°C for 45 min, dried at 150°C for 1.5 h under a nitrogen atmosphere, heated to 320°C and kept at that temperature for 1.5 h. (3) A mixed gas is introduced, and carbonitriding is performed at 490°C with a voltage of 500V and a frequency of 80Hz and kept at that temperature for 5.5 h to obtain the base metal connector A. Step 3: (1) Add 28 parts nickel sulfate, 26 parts sodium hypophosphite, 22 parts lactic acid, 15 parts succinic acid, 0.065 parts lanthanum nitrate, and 0.002 parts thiourea to 135 parts deionized water, adjust the pH to 5.5, mix at 40°C to obtain a chemical plating solution; (2) Immerse the base metal connector A in hydrochloric acid aqueous solution, acid-wash and activate at 60°C for 12.5 min, wash with deionized water, chemically plating at 85°C for 2 h using the chemical plating solution, and then heat-treat at 400°C for 1 h under a nitrogen atmosphere to obtain the metal connector.

[0033] Comparative Example 4: Based on Example 1, the pretreatment temperature was adjusted while the rest of the process remained unchanged, specifically: Step 1: Roll the base steel at 1000℃, then anneal at 900℃, cool to 600℃, quench at 875℃ using brine as the quenching medium, and finally temper at 225℃ and cool to obtain the base metal connector. Step 2: (1) Glycine, urea, lanthanum lactate, disodium ethylenediaminetetraacetate, and deionized water are mixed in a mass ratio of 2:1:0.4:0.1:45. Acetic acid is added to adjust the pH to 5.0 to obtain a composite complexing agent. (2) The composite complexing agent is sprayed onto the surface of the base metal connector at a rate of 1.1 ml / min for 8 min. Under a nitrogen atmosphere, the temperature is raised to 320°C and kept at that temperature for 1.5 h. (3) A mixed gas is introduced, and carbonitriding is performed at 490°C with a voltage of 500 V and a frequency of 80 Hz for 5.5 h to obtain the base metal connector A. Step 3: (1) Add 28 parts nickel sulfate, 26 parts sodium hypophosphite, 22 parts lactic acid, 15 parts succinic acid, 0.065 parts lanthanum nitrate, and 0.002 parts thiourea to 135 parts deionized water, adjust the pH to 5.5, mix at 40°C to obtain a chemical plating solution; (2) Immerse the base metal connector A in hydrochloric acid aqueous solution, acid-wash and activate at 60°C for 12.5 min, wash with deionized water, chemically plating at 85°C for 2 h using the chemical plating solution, and then heat-treat at 400°C for 1 h under a nitrogen atmosphere to obtain the metal connector.

[0034] Comparative Example 5: Based on Example 1, lanthanum nitrate was removed from the electroless plating solution, while the rest of the process remained unchanged. Specifically: Step 1: Roll the base steel at 1000℃, then anneal at 900℃, cool to 600℃, quench at 875℃ using brine as the quenching medium, and finally temper at 225℃ and cool to obtain the base metal connector. Step 2: (1) Glycine, urea, lanthanum lactate, disodium ethylenediaminetetraacetate and deionized water are mixed in a mass ratio of 2:1:0.4:0.1:45. Acetic acid is added to adjust the pH to 5.0 to obtain a composite complexing agent; (2) The composite complexing agent is sprayed onto the surface of the base metal connector at 1.1 ml / min for 8 min. It is ultrasonically treated at 80℃ for 45 min, dried at 150℃ for 1.5 h under nitrogen atmosphere, heated to 320℃ and kept at that temperature for 1.5 h; (3) Mixed gas is introduced and carbonitrided at 490℃ with a voltage of 500V and a frequency of 80Hz and kept at that temperature for 5.5 h to obtain base metal connector A; Step 3: (1) Add 28 parts nickel sulfate, 26 parts sodium hypophosphite, 22 parts lactic acid, 15 parts succinic acid, and 0.002 parts thiourea to 135 parts deionized water, adjust the pH to 5.5, mix at 40°C to obtain a chemical plating solution; (2) Immerse the base metal connector A in hydrochloric acid aqueous solution, pickle and activate at 60°C for 12.5 min, wash with deionized water, perform chemical plating at 85°C for 2 h using the chemical plating solution, and then heat treat at 400°C for 1 h under nitrogen atmosphere to obtain the metal connector.

[0035] Test experiment: The high-strength wear-resistant metal connectors prepared in Examples 1-3 and Comparative Examples 1-5 were tested for their performance: (1) Strength test: The high-strength wear-resistant metal connectors prepared in Examples 1-3 and Comparative Examples 1-5 were tested for impact toughness in accordance with GB / T 229-2020 Charpy impact test method for metallic materials. The higher the impact toughness, the better the strength. The test results are shown in Table 1; (2) Wear resistance test: The hardness of the connectors prepared in Examples 1-3 and Comparative Examples 1-5 was tested in accordance with GB / T 231.1-2018 Brinell hardness test for metallic materials. The higher the hardness, the better the wear resistance. The test results are shown in Table 1;

[0036] Results Analysis: Analysis of the data in Table 1 shows that, according to Comparative Example 1, removing lanthanum lactate from the composite complexing agent prevents synergistic effects with glycine and urea, resulting in coarse grains and decreased hardness and impact toughness. According to Comparative Example 2, removing glycine and urea from the composite complexing agent fails to remove the surface oxide film and provide subsequent carbon and nitrogen sources, leading to decreased hardness and impact toughness. According to Comparative Example 3, excessive lanthanum lactate in the composite complexing agent forms a diffusion barrier, hindering the diffusion of carbon and nitrogen elements, resulting in decreased hardness and impact toughness. According to Comparative Example 4, adjusting the pretreatment temperature prevents stepwise action, leading to uneven carbon-nitrogen co-diffusion, stress concentration, and decreased hardness and impact toughness. According to Comparative Example 5, removing lanthanum nitrate from the electroless plating solution decreases electroless plating stability, reduces deposition rate, weakens interfacial adhesion, makes it prone to peeling, and decreases hardness and impact toughness.

[0037] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A processing technology for a high-strength, wear-resistant metal connector, characterized in that: Includes the following steps: Step 1: Roll, heat treat, and cool the base steel to obtain the base metal connector; Step 2: Spray the composite complexing agent onto the surface of the base metal connector for pretreatment, followed by carbonitriding, to obtain base metal connector A; Step 3: Apply a surface coating to the base metal connector A and perform post-processing to obtain the metal connector.

2. The processing technology of a high-strength wear-resistant metal connector according to claim 1, characterized in that: The raw materials of the base steel include the following elements, by mass percentage: 0.65%~0.70% carbon, 1.00%~1.25% silicon, 0.45%~0.60% manganese, ≤0.025% sulfur, ≤0.025% phosphorus, 0.40%~0.50% molybdenum, 0.10%~0.30% chromium, 0.15%~0.25% vanadium, with the remainder being iron.

3. The processing technology of a high-strength wear-resistant metal connector according to claim 1, characterized in that: The preparation process of the composite complexing agent is as follows: glycine, urea, lanthanum lactate, disodium ethylenediaminetetraacetate, and deionized water are mixed in a mass ratio of 2:1:0.3~0.5:0.05~0.15:40~50, and acetic acid is added to adjust the pH to 4.5~5.5 to obtain the composite complexing agent.

4. The processing technology of a high-strength wear-resistant metal connector according to claim 1, characterized in that: In step 1, the rolling temperature is 950~1050℃; in the heat treatment, the process parameters include: annealing temperature is 850~920℃, cooling temperature is 550~650℃, quenching temperature is 850~900℃, quenching medium is brine; tempering temperature is 200~250℃.

5. The processing technology of a high-strength wear-resistant metal connector according to claim 1, characterized in that: In step 2, the spraying process parameters are: spraying flow rate of 0.5~1.8 ml / min; spraying time of 5~10 min; The pretreatment process parameters are as follows: ultrasonic treatment temperature is 75~85℃, ultrasonic treatment time is 30~60min; the atmosphere is nitrogen atmosphere, drying temperature is 140~160℃, drying time is 1~2h; heating temperature is 240~400℃; heat preservation time is 1~2h. The process parameters for carbonitriding are as follows: atmosphere is a mixed gas; voltage is 450~550V; frequency is 75~85Hz; carbonitriding temperature is 400~580℃; and holding time is 5~6h.

6. The processing technology of a high-strength wear-resistant metal connector according to claim 5, characterized in that: The initial volume ratio of the mixed gas is nitrogen and hydrogen at 1:4~5; it is dynamically adjusted to a volume ratio of 4~5:

1.

7. The processing technology of a high-strength wear-resistant metal connector according to claim 1, characterized in that: In step 3, the surface coating process is as follows: immerse the base metal connector A in hydrochloric acid aqueous solution, pickle and activate it at 55~65℃ for 10~15min, wash with deionized water, and perform chemical plating at 80~90℃ for 1~3h. The post-treatment process is as follows: heat treatment at 350~450℃ for 0.5~1.5h under a nitrogen atmosphere.

8. The processing technology of a high-strength wear-resistant metal connector according to claim 7, characterized in that: The preparation process of the chemical plating solution is as follows: nickel sulfate, sodium hypophosphite, lactic acid, succinic acid, lanthanum nitrate, and thiourea are added to deionized water, the pH is adjusted to 5.2~5.7, and the mixture is mixed at 35~45℃ to obtain the chemical plating solution.

9. The processing technology of a high-strength wear-resistant metal connector according to claim 8, characterized in that: The raw materials of the chemical plating solution include the following components by mass: 27-29 parts nickel sulfate, 25-27 parts sodium hypophosphite, 20-24 parts lactic acid, 13-17 parts succinic acid, 0.05-0.08 parts lanthanum nitrate, 0.001-0.003 parts thiourea, and 120-150 parts deionized water.

10. A high-strength wear-resistant metal connector is prepared by the processing technology according to any one of claims 1 to 9.